Variations of induction vector in North America - V. Babak; I. Rokityanskiy; A. Tereshyn (Геофизический журнал, 2014)
The results of the magnetovariational data processing of 13 observatories in North America for 24 years are presented. In addition to the annual variation of the induction vectors, which is widely known, 11-year periodicity is found. It is a new geophysical phenomenon. While looking for precursory signals associated with earthquakes, these periodic variations must be taken into account.